The Effect of Teachers’ Use of Deixis on Students’ Understanding of Their Talk - Jumaedah, Ninik; Saleh, Mursid; Hartono, Rudi (English Education Journal, 2020)
Language is crucial in human life as it cannot be separated from human being. People could deliver his or her thought by using language. Deixis is defined as words used to point on something that depends on the context. According to Levinson the single most obvious way in which the relationship between language and context is reflected in the structures of language themselves, is through the phenomenon of deixis. The aim of this study is to investigate the topic based on the observation, the realization of deixis also existed in education. The phenomenon occured when the English teacher explained the lessons in a classroom during the teaching learning process in SMA Islam Sultan Agung 3 Semarang. In obtaining the data, The research design used in this study was a qualitative research (particularly, a classroom analysis) supported by a bit of quantitative data. The object of the study comprised two things, namely teachers’ and students’ use of deixis in their talk. Person deixis was dominant used by interaction in class between students and English teacher of their talk. the teacher’s questionnaire could be said as valid.. The rtableused was 0.878 since the sample size was two teachers. And then, the students questionnaire was also valid. the rtableused was 0.388 since the sample size was thirty students. Pre-test were 46.6. After doing the same calculation procedures as to the post -test, the researcher found that the students’ mean score 81.0 from the data.